Enhanced the accuracy of idle time in cognitive radio network - Mohamad, Mas Haslinda; Sali, Aduwati; Nordin, Rosdiadee (Universitas Ahmad Dahlan (UAD), 2021)
This paper addresses the essential part of modelling primary user (PU) activity pattern in the time domain, which involved choosing the best distribution fit to represent idle and busy time. The accurate PU activity model plays a vital role in developing high-performance cognitive radio (CR) network. This work formulates the PU activity model by using the empirical data measured from wireless local area network (WLAN) testbed. The detected idle time analysed in this work in two different scenarios, then a statistical approach performed to find the best fits. The finding shows the generalised Pareto (GP) distribution as the best fit with DKS=0.266 compared to other distribution fits.